“What women want”: Focus group discussions to inform the design of nutrition resources for women impacted by menopause following cancer treatment - Samantha J. Cushen; Micheala Murphy; Katie E. Johnston (Clinical Nutrition Open Science)
Summary: Background and Aims: Menopause, as a direct result of cancer treatment, is a significant issue facing many female survivors. Uncertainty related to dietary choices to manage menopausal symptoms can be distressing for female cancer survivors, potentially increasing the risk of developing comorbid conditions and reducing quality of life. The aim of this study was to assess the burden of menopausal symptoms, explore the nutritional information needs of cancer survivors and their preferences for the mode of delivery to inform future interventions on nutrition. Methods: A qualitative study using focus groups (n=3) was conducted with female cancer survivors (aged ≥18 years). Cancer survivors were defined as women diagnosed with cancer at any stage, including those undergoing active treatment or with a past cancer history, who were experiencing menopausal symptoms as a result of their cancer treatment. Results: Participants (n=16) were survivors of breast (n=14), ovarian (n=1) and endometrial (n=1) cancer. Mean age was 50.4 years (SD= 6.4). Four major themes emerged: (i) desire for control (ii) menopausal symptom management (iii) participants feeling lost during survivorship and (iv) the need for accessible, and tailored nutrition resources. Conclusions: Managing menopausal symptoms post-treatment can be difficult and burdensome for cancer survivors, affecting their quality of life. These women report feeling lost with significant needs for information on nutrition and supplementation related to recovery and symptom management. These women desire a menopause specific nutrition resource that is evidence-based and tailored to the needs of cancer survivors.